Success Information System Analysis in Dapodikdas Purbalingga Using Delone and Mclean Model - Dwi Krisbiantoro; Retno Waluyo (JUITA : Jurnal Informatika, 2017)
This study aims to analyze the relationship between the variables determining the success of information systems proposed by DeLone and McLean on the information system of DAPODIKDAS. Data collection technique used was questionnaire. Hypothesis testing used was with simple regression analysis technique. The biggest variable relation was the relationship between Service Quality variables and Intention to Use, while the biggest variable influence was the influence of Service Quality variables on Intention to Use. The smallest variable relationship was the relationship between intention to use variables against Net Benefit, while the smallest variable influence was the influence of Intention to Use variables against Net Benefit.